Evaluasi Pembelajaran Non Tes Dalam Pembelajaran Fiqh SMAN 1 Nguntoronadi - Firmansyah, Sheva Bayu; Rudiana, Reva Ananda; Zidane, Alfian Muchammad (Faidatuna, 2024)
This research aims to find out how non-test learning activities and evaluation are implemented at SMAN 1 Nguntoronadi. This research uses a qualitative approach and uses descriptive methods. The technique used is an interview with a PAI teacher with the initials R. The interview is carried out by preparing questions according to the desired answers and then conveying them to the resource person. The results of this research show that PAI teachers have carried out non-test learning activities, especially in fiqh subjects. The form of non-test activity carried out is making presentations and practicing on fiqh chapters. Evaluation is carried out through an assessment rubric that has been created as well as a special task carried out by PAI teachers, namely consciously keeping a journal about students' daily behavior in school. Then, if someone does not meet the assessment, they will be given an assignment. The obstacles experienced are related to the duration of preparation for non-test learning activities and the condition of the students.